2432. Appropriateness of Empiric Extended-Infusion Piperacillin/Tazobactam in the Intensive Care Unit. (26th November 2018) - Tucker, Kendall; Benning, Molly; Ryan, Keenan; Walraven, Carla; Jakeman, Bernadette
Abstract: Background: Gram-negative (GN) infections in ICU patients have increased antibiotic resistance owing to higher minimum inhibitory concentrations (MICs). Piperacillin/tazobactam (PTZ) 3.375 g extended infusion (EI) may be used as an empiric agent. GN organisms with PTZ MICs > 16/4 may not be adequately covered by this regimen. The objective of this study was to evaluate MICs of GN isolates from the ICU to determine whether PTZ 3.375 g EI is an appropriate empiric regimen for ICU patients. Appropriateness of empiric antibiotic therapy was defined as PTZ MIC ≤16/4 in greater than 80% of isolates. The secondary objective was to evaluate patient specific risk factors that may be associated with elevated PTZ MICs in GN pathogens. Methods: All ICU patients admitted from January to December 2017 with a confirmed GN pathogen from a non-urinary source were included. Patients were excluded if they had cystic fibrosis, cultures obtained >48 hours prior to ICU admission, or they were incarcerated. Patients' electronic medical records were reviewed for the following data: age, sex, ethnicity, location prior to ICU admission, GN pathogen, culture source, risk factors for multi-drug-resistant organisms (dialysis, injection drug use, indwelling catheter, wounds/trauma), pathogen susceptibility profile, risk modifying co-morbidities (diabetes, heart failure, chronic kidney disease, and liver disease) and creatinine clearance. Results: 231 patients were included in the study. The average patient was 56.7 years old ±16.95. The majority of patients were white (64.1%) and male (69.7%). There were no significant differences in baseline characteristics between patients with PTZ MICs >16/4 and those with MICs ≤16/4. Pseudomonas aeruginosa (41%) was the primary organism identified and 28% of all GN isolates had MICs >16/4. Dialysis ( P = 0.028), IV antibiotics ( P < 0.001) and presence of wounds or trauma ( P = 0.018) were all associated with elevated MICs. Conclusion: Current PTZ EI 3.375g dosing may not provide adequate empiric coverage of GN pathogens for ICU patients especially for patients who received previous IV antibiotics, are on dialysis, or have the presence of wounds or trauma. Disclosures: All authors: No reported disclosures.